2021
DOI: 10.3389/fcvm.2021.654254
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Cullin 3 Ligase Signaling Pathways Contributes to Hypertension in Preeclampsia

Abstract: Background: Preeclampsia (PE) is a leading cause of maternal and perinatal morbidity and mortality; however, its etiology and pathophysiology remain obscure. PE is initiated by inadequate spiral artery remodeling and subsequent placental ischemia/hypoxia, which stimulates release of bioactive factors into maternal circulation, leading to hypertension and renal damage.Methods and Results: Abundance of key components of cullin 3-ring ubiquitin ligase (CRL3), including cullin 3 (CUL3) and its neddylated modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Recent work from the Fenton group suggests neddylation of several cullins, including CUL3 changes in dietary K + intake in mice, 42 (preprint) pointing to a possible role for modulation of JAB1 activity under normal physiologic conditions. Dysregulation of CUL3 neddylation may also contribute to diabetic kidney disease, because KLHL3 abundance is lower in db/db diabetic mice, 14 in streptozotocin-induced type 1 diabetic mice, 15 and in a mouse model of pre-eclampsia, 43 with increased NCC phosphorylation observed in all three models. We also reported that renal tubular Cul3 −/− mice develop renal fibrosis, and that lower CUL3 abundance is observed in several mouse renal injury models 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work from the Fenton group suggests neddylation of several cullins, including CUL3 changes in dietary K + intake in mice, 42 (preprint) pointing to a possible role for modulation of JAB1 activity under normal physiologic conditions. Dysregulation of CUL3 neddylation may also contribute to diabetic kidney disease, because KLHL3 abundance is lower in db/db diabetic mice, 14 in streptozotocin-induced type 1 diabetic mice, 15 and in a mouse model of pre-eclampsia, 43 with increased NCC phosphorylation observed in all three models. We also reported that renal tubular Cul3 −/− mice develop renal fibrosis, and that lower CUL3 abundance is observed in several mouse renal injury models 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we propose for future studies a possible implication of non-coding RNAs including micro RNAs (miRNAs) and long non-coding RNAs (lncRNAs), whose relevance in the regulation of oxidative stress and potential translational applications has been previously reported [ 52 , 53 , 54 , 55 ]. However, prior works have also described altered levels of Keap1 and CUL3 in other pregnancy complications, such as preeclampsia, suggesting its potential role in the pathophysiology of obstetric diseases [ 56 , 57 ]. This could entail possible pathophysiological consequences observed in the placenta of women with CVD.…”
Section: Discussionmentioning
confidence: 99%